Development of red-shifted and fluorogenic nucleoside and oligonucleotide diarylethene photoswitches - Kolmar, Theresa; Becker, Antonia; Pfretzschner, Ronja A.; Lelke, Alina; Jäschke, Andres (Chemistry - a European journal, 2021)
The reversible modulation of fluorescence signals by light is of high interest for applications in super-resolution microscopy, especially on the DNA level. In this article we describe the systematic variation of the core structure in nucleoside-based diarylethenes (DAEs), in order to generate intrinsically fluorescent photochromes. The introduction of aromatic bridging units resulted in a bathochromic shift of the visible absorption maximum of the closed-ring form, but caused reduced thermal stability and switching efficiency. The replacement of the thiophene aryl unit by thiazol improved the thermal stability, whereas the introduction of a benzothiophene unit led to inherent and modulatable turn-off fluorescence. This feature was further optimized by introducing a fluorescent indole nucleobase into the DAE core, resulting in an effective photoswitch with a fluorescence quantum yield of 0.0166 and a fluorescence turn-off factor of 3.2. The site-specific incorporation into an oligonucleotide resulted in fluorescence-switchable DNA with high cyclization quantum yields and switching efficiency, which may facilitate future applications.
Gesehen am 27.03.2023